IFN-β is a macrophage-derived effector cytokine facilitating the resolution of bacterial inflammation - Senthil Kumaran Satyanarayanan (Nature Portfolio, 2019)
Clearance of apoptotic neutrophils by macrophages is important for the resolution of inflammation. Here, the authors show that interferon-β produced by resolution phase macrophages promotes neutrophil apoptosis and efferocytosis and induces macrophage reprogramming to a pro-resolving phenotype, thereby identifying IFN-β as a multi-pronged pro-resolution cytokine.